Sorption Efficiencies and Capacities for Removal of Cu2+ by Particles of Ignimbrite: Equilibrium and Thermodynamic Studies - Oguz, Ensar (Asian Journal of Chemistry, 2014)
In this manuscript, Cu2+ uptake by the particles of ignimbrite from aqueous solutions was investigated using batch sorption techniques. The sorption equilibrium studies were performed as a function of contact time, initial Cu2+ concentration, sorbent dosage, pH, temperature and agitation rate. The removal efficiency of Cu2+ and maximum Cu2+ sorption capacity of the ignimbrite particles were 76 % and 1.64 (mg m-2), respectively. To evaluate the sorption equilibrium, four isotherm models were fitted to experimental data. The best model was determined by taking into account the correlation coefficient (R2). The best adjustment from isotherm models was observed to be the Langmuir (R2 0.973). The activation energy (Ea) was determined as 9.9 kJ mol-1. Thermodynamic parameters such as DH°, DS° and DG° were calculated from the slope and intercept of linear plot of ln KD versus 1/T. The DH° and DG° values of Cu2+ sorption on the particles of ignimbrite show endothermic heat of sorption. The results indicated that the particles of ignimbrite are suitable sorbents in the removal of Cu2+ ions from an aqueous solution.